Successful percutaneous drainage of a refractory caudal mediastinal paraesophageal abscess in a dog. Issue 4 (21st February 2021) - Breheny, Craig R.; Thomas, Emily K.; Hall, Jon L.; Thierry, Florence
Abstract: Objective: To describe a novel technique for paraesophageal abscess drainage in a dog. Case summary: A 6‐year‐old dog presented for pyrexia of unknown origin, subsequently confirmed to be due to a paraesophageal abscess. This was managed by the ultrasound‐guided placement of a thoracostomy tube into the abscess, allowing drainage to be performed. This led to clinical resolution and, at an 8‐month follow‐up, the dog continued to do well. New or unique information provided: Paraesophageal abscessation is typically managed with surgical intervention, which carries inherent risks and complications. This report describes a novel technique that did not require general anesthesia or invasive surgical intervention, achieving clinical remission without any adverse effects. It also summarizes the current literature available on this condition.